Morphology and molecular organization of the adult neuromuscular junction of Drosophila. - Rivlin, P.K.; St. Clair, R.M.; Vilinsky, I.; Deitcher, D.L. (Journal of Comparative Neurology, 2004)
While the larval neuromuscular junction (NMJ) of Drosophila has emerged as a model system to study synaptic function and development, little attention has been given to the study of the adult NMJ. Here we report an immunocytochemical and morphological characterization of an adult NMJ preparation of the prothorax. All muscles examined were innervated by small, uniform type II terminals (0.5-1.5 microm), a subset of which contained octopamine. Terminals classified as type I varied in their morphology across different muscles, ranging from strings or clusters of boutons (0.8-5.5 microm) to an elongate terminal (80-100 microm long) with few branches and contiguous swellings (3-15 microm) along its length. Analysis of the molecular composition of the NMJs during the first 5 days after eclosion revealed four major findings: 1) type I boutons increase in size during early adulthood; 2) Fasciclin II-immunoreactivity is not detectable at type I terminals, while DLG-immunoreactivity is observed at the synapse; 3) a Shaker-GFP fusion protein that localizes to all type I boutons in the larva is differentially localized at adult prothoracic NMJs; and 4) while all type I terminals contain glutamate, the glutamate receptor subunits, DGluRIIA and DGluRIIB, are expressed and clustered in only a subset of muscles. These findings suggest that maturation of the adult NMJ occurs during early adulthood and that muscle-specific properties may play a role in organizing synaptic components in the adult. Furthermore, these results demonstrate that there are major differences in the molecular organization of the adult and larval NMJs.